Finding Your Leading Man: How to Create Male-to-Male Intimacy and Make Your Relationship a Blockbuster - Bloch, Jon P. (St. Martin's Griffin, 2000)
Keywords: Gay men; Interpersonal relations; Intimacy (Psychology); dept.soc; faculty_collection

Sociology: An Introduction - Doob, Christopher Bates; Faupel, Charles E. (Harcourt Press, 2000)
Keywords: Sociology; dept.soc; faculty_collection

Justice for the Poor: A Case Study of Criminal Defense Work. - Emmelman, Debra S. (Fall; Sociology/Anthropology., 2000)
Keywords: dept.soc

Book Review: Superpredators: The Demonization of Our Children by the Law, by Peter Elikann, Perseus Publishing, 1999. - Kenty, Jessica L. (Bimonthly Review of Law Books, 2000)
Keywords: book.review; dept.soc; ⛔ No DOI found

The new and improved clint eastwood: change and persistence in promise keepers self-help literature - Bloch, Jon P (Sociology of Religion, 2000)
Like other expressions of Christian conservatism, the Promise Keepers (PK) often enact complex and strained relationships between social change and social persistence. These strains are evident in the official PK literature, which employs techniques not unlike those used by mainstream pop psychology. These include the use of “scientific”-like classifications of information, authors presented as “experts” on the topic at hand, and the use of exercises to be enacted individually or in small PK discussion groups. Collectively, these strategies suggest that conservative Christians deal with many of the same complex role demands as non-conservatives. In Particular, the PK stance on gender roles, though Promoted as unambiguously “traditional” in favoring male leadership and female submission, in actuality often reflects acknowledgment and perhaps acceptance of some of the more egalitarian changes in gender role norms. Sociological implications and directions for future research are discussed.
13 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/070-278-825-342-722 tex.type: [object Object]
Keywords: dept.ant; dept.soc